Evaluating Web Sites through the use of Focus Group Interviews - Wendy-Lin Bartels; Marshall Breeze; Nancy Peterson (EDIS, 2003)
This publication was produced by the Center for Natural Resources at the University of Florida. CNR 14 is part of a Program Summary Series. First published: 11/25/2002, Minor revision: March 2003.